Going Online to Make Learning Count - Brigham, Cathy; Klein-Collins, Rebecca (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Adult students often come to higher education with college-level learning that they have acquired outside of the classroom – from the workplace, military service, self-study, or hobbies. For decades, many forward-thinking colleges and universities have been offering services to evaluate that learning and award it college credit that counts towards a degree. However, for a range of reasons, not every institution can offer prior learning assessment (PLA) in every discipline or for every student. With funding from several U.S. philanthropic organizations, the Council for Adult and Experiential Learning (CAEL) is launching Learning Counts, a national online service that will offer students a range of opportunities to have their learning evaluated for college credit. This online service will expand the capacity of institutions offering PLA to students and provide an efficient and scalable delivery mechanism for the awarding of credit through PLA.